Hubungan Kadar Enzim Transaminase Pasien COVID-19 dengan Derajat Keparahan Penyakit di RSUP Dr. M. Djamil Padang - Rahmadina, Rahmadina; Herman, Deddy; Efrida, Efrida; Almurdi, Almurdi; Russilawati, Russilawati; Elvira, Dwitya (Faculty of Medicine, Universitas Andalas, 2024)
Liver injury can be caused by coronavirus disease 2019 (COVID-19), characterized by increased levels of transaminase enzymes (aspartate aminotransferase/AST and alanine aminotransferase/ALT). Objective: To determined the correlation between transaminase enzyme levels and the severity of COVID-19 in Dr. M. Djamil Central Public Hospital, Padang. Methods: This was an observational analytic study with a cross-sectional design. Data were obtained randomly from medical records of confirmed COVID-19 patients hospitalized in Dr. M. Djamil Hospital from June to August 2021, with moderate, severe, and critical severity based on Indonesian Ministry of Health criteria. Data were analyzed using the Chi-square test to examine the distribution and correlation between variables and a simple logistic regression test to assess the level of risk between variables. Results: 57,80% had abnormal AST, and 44,95% had abnormal ALT. The median AST was highest in the critical group, while the median ALT was highest in the severe group. The distribution of sex and age group were significantly different based on AST and ALT levels, and the distribution of patients with coronary heart disease was significantly different based on ALT levels. Transaminase enzyme levels had a significant correlation with the severity of COVID-19 (p-value = 0,00). Patients with critical degrees had the highest risk for abnormal AST and severe degrees had the highest risk for abnormal ALT. Conclusion: Transaminase enzymes have a significant correlation with the severity of COVID-19.Keywords: Â COVID-19, liver injury, transaminases, disease severity